Reactive splicing compatibilization of immiscible polymer blends: Compatibilizer synthesis in the melt state and compatibilizer architecture effects. (17th December 2019) - Wei, Bin; Lin, Qingqing; Zheng, Xin; Gu, Xiaoying; Zhao, Li; Li, Jianchun; Li, Yongjin
Abstract: Reactive compatibilization is an effective method to improve the compatibility of immiscible polymer blends. The in-situ-formed graft/block copolymers should be thermodynamically located at the interface to bridge the neighboring phases. Unfortunately, they are often pulled out of the interface because of the asymmetric molecular structures. Here, we propose a new strategy to compatibilize immiscible polymer blends called reactive splicing compatibilization. Poly (styrene- co -glycidyl methacrylate) (SG) with high glycidyl methacrylate (GMA) content is used as the reactive backbone chain. Both poly (l -lactic acid) (PLLA) and poly (butylene adipate-co-terephthalate) (PBAT) molecular chains can be easily grafted onto the SG main backbone by the reaction of the terminal carboxylic acid groups with the epoxide groups in the melt. Direct melt blending SG with PLLA and/or PBAT leads to reactive compatibilizers with various molecular architectures, which are used for subsequent compatibilization of PLLA/PBAT blends. It was found that the compatibilizer architecture significantly affects the compatibilization efficiency. The best compatibilization occurs with a reactive compatibilizer of SG-g-PBAT with the SG to PBAT weight ratio of 1:2. The compatibilized PLLA/PBAT (50/50 w/w) blend has precise co-continuous phase morphology with very few micelles. The blend exhibits extremely high Charpy notched impact strength of 90.2 kJ/m 2 and tensile strength of 33.3 MPa. The principle of the facile splicing compatibilization strategy is highly applicable to many other immiscible blends with both components containing reactive groups. Graphical abstract: We report the splicing compatibilization strategy for immiscible polymer blends. The compatibilizer architecture effects on the compatiblization efficiency were investigated. Image 1 Highlights: New compatibilization strategy called reactive splicing compatibilization was proposed. Reactive comb compatibilizers with various architectures were synthesized by melt blending. Molecular architecture effects on compatibilization of PBAT/PLLA blends were investigated. PLLA/PBAT blends with superior toughness and high tensile strength were prepared.